2012
DOI: 10.1186/2050-6511-13-s1-a39
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions and polypharmacy in cardiac patients

Abstract: Background Adverse drug reactions (ADR) appear more frequently then what is actually reported and registered. The aim was to establish an intensive monitoring system and to analyze ADR in hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…23 There are also reports stating a higher incidence of ADRs in contrast with the present findings. [24][25] In 3.88% of cases, patients were hospitalized due to ADRs which was supported by a study conducted by Arulmani et al (3.4%). 26 However, a higher incidence (6.4%) was seen in a study carried out by Kaur et al 18 There were 60 patients (19.42%) who developed a total of 93 ADRs during their hospital stay.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…23 There are also reports stating a higher incidence of ADRs in contrast with the present findings. [24][25] In 3.88% of cases, patients were hospitalized due to ADRs which was supported by a study conducted by Arulmani et al (3.4%). 26 However, a higher incidence (6.4%) was seen in a study carried out by Kaur et al 18 There were 60 patients (19.42%) who developed a total of 93 ADRs during their hospital stay.…”
Section: Discussionmentioning
confidence: 53%
“…The finding of the present study is comparable to that of earlier studies where polypharmacy was the only predictor for ADRs. 25,34 On evaluation of drug class implicated in ADRs, betablockers (14.68%) were the most common drug class followed by Renin-Aldosterone-Angiotensen-Receptors (RAAS) blockers and anti-coagulants. The present findings are similar to the findings reported in studies conducted by Haile et al and Chan et al 3,31 In contrast to these findings, a study conducted by Rohit et al reported that calcium channel blockers were the most common drug class involved in ADRs.…”
Section: Discussionmentioning
confidence: 99%